The Role Of Periapical Radiography In Identifying Channel Configurations Type II Vertucci Root In The First Premolar Tooth Of The Maxim - Radetyo Bhumyang Pandu Wirayudha; Nilasary Rochmanita Suparno; Aditya Varenka Putra Niardhy; Cahyani Cahyani (International Journal of Health Engineering and Technology, 2026)
The first premolar maxillary has a complex diversity of root canal configurations. Identification of the proper root canal configuration greatly determines the success of endodontic treatment. Periapical radiography remains an easily accessible and useful examination to detect the possibility of more than one root canal through radiograph retrieval with the principle of Same Lingual Opposite Buccal, i.e. horizontal angulation changes and canal shadow variation analysis. To report the role of periapical radiography in identifying the configuration of the Vertucci root canal type II in the first premolar of the maxillary and its implications for endodontic management. A 39-year-old male came in with a complaint of cavities in the first premolar tooth of the left maxillary (Tooth 24). Initial periapical radiographs show the suspicion of the presence of more than one root canal. Taking radiographs with angulation variations helps to clarify the relationship of the root canal, which appears to be separate in the coronal and middle part of the root and then merge before reaching the apex, according to the Vertucci type II configuration. The radiography findings were used as a basis for determining treatment strategies and were confirmed on postoperative radiographs. Periapical radiography with angulation variations and SLOB principles remains valuable in detecting type II Vertucci configurations and aiding in the planning and implementation of more accurate root canal treatments.